Newborn Weight and Second-Hand Smoking in Utero Exposure: A Case in A Low-Middle Income Country - Sugiyo, Dianita; Supriyatiningsih, Supriyatiningsih; Sutantri, Sutantri; Sutrisno, Resti Yulianti; Indriastuti, Nur Azizah; Aditjondro, Enrico; Yuswatiningsih, Endang; Helmi, M; Wandasari, Noven Tri; Tanjung, Afriansyah; Afghani, Soewardiman Al; Satria, Faudyan Eka; Hapsari, Saphira Hanan; Samsudin, Mohammad Agus; Rachmawati, Riska Putri (Fakultas Ilmu-ilmu Kesehatan, 2023)
Smoking exposure among pregnant women is correlated with the risk of low birth weight. The policy factors are believed to contribute to the rate or prevalence of smoking activities. This study aims to simultaneously portray the incidence of low-birth-weight newborns correlated with smoking exposure. The samples were 160 respondents, with 57 and 103 respondents in Hospital A and G respectively. A mixed-method analysis was utilized by combining a retrospective approach to identify the key findings and be equipped with a narrative analysis of the socio-demographic - law enforcement process. The Spearman correlation analysis was used for investigating correlation among variables. Spearman correlation test smoking exposure per day in minutes (rho= -0.595, p<0.001) and the number of smokers (rho= -0.621, p<0.001) for Hospital A, and smoking exposure per day in minutes (rho= -0.681, p<0.001) and the number of smokers (rho= -0.613, p<0.001) for Hospital G. It implied a strong correlation of inverse relationship among those variables. Smoke-free law enforcement is a key point to address, aiming at vulnerable group protection, including pregnant mothers and babies. The local government should consider the effects affected by smoking behavior in the community.